2017
DOI: 10.1021/acs.est.6b05404
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Microcystin Exposure Increases Liver Injury Risk Induced by Hepatitis B Virus Combined with Aflatoxin: A Cross-Sectional Study in Southwest China

Abstract: Three liver hazards, two confirmed-hepatitis B virus (HBV) and aflatoxin (AFB), and one rarely studied in populations-microcystin (MC), simultaneously exist in tropical and humid areas; however, there are no epidemiological data on their risks in the same population. We conducted a community-based cross-sectional survey among 5493 adults in two rural towns and statistically analyzed the comparative and combinative effects of the three factors after detecting HBsAg and HBV DNA titers, determining estimated dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…Instead, exposure to AFB1 would also exacerbate and accelerate the disease progression of HBV infection, perhaps via affecting susceptibility to infection or viral replication . In tropical and humid area such as Southern China, many people are chronically infected with HBV while also exposing AFB1 in their diet . Individuals with HBV infection were much more susceptible to AFB1‐associated HCC risk compared with those without these aetiological factors .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, exposure to AFB1 would also exacerbate and accelerate the disease progression of HBV infection, perhaps via affecting susceptibility to infection or viral replication . In tropical and humid area such as Southern China, many people are chronically infected with HBV while also exposing AFB1 in their diet . Individuals with HBV infection were much more susceptible to AFB1‐associated HCC risk compared with those without these aetiological factors .…”
Section: Discussionmentioning
confidence: 99%
“…For example, exposure to 0.5 and 1 mg/kg of AFB1 for 7 days induced liver damage and dysregulation of genes associated with lipid metabolism in rats . Notably, HBV‐infected patients would be more susceptible to liver injury induced by AFB1 . However, just one study in zebrafish showed that combination of HBx and AFB1 promoted hepatic steatosis and increased the expression of lipogenic factors and genes related to lipid metabolism yet .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study, conducted in a general population in the Three Gorges region, found that estimated daily intake of microcystins was positively correlated with liver injury in Chongqing, a warm and humid area with severe microcystin and aflatoxin contamination in southwest China . In our recently published article, we found that microcystins may have the potential to increase the risk of liver injury induced by combined exposure to HBV and aflatoxin …”
mentioning
confidence: 89%
“…(19,20) In our recently published article, we found that microcystins may have the potential to increase the risk of liver injury induced by combined exposure to HBV and aflatoxin. (21) Currently, there is no direct linkage between microcystins and HCC risk due to a lack of extensive epidemiological data on serum MC-LR in human. Therefore, we embarked on a case-control study to determine serum MC-LR so as to assess the independent effects of MC-LR and its interaction effects with the known risk factors for HCC risk in southwest China.…”
mentioning
confidence: 99%
“…Microcystin-LR (MC-LR), a toxin that is produced by cyanobacteria Microcystis aeruginosa, has been observed to possibly increase the liver damage risk in people suffering from hepatitis B simultaneously exposed to AFB 1 [94]. Enhanced effects of AFB 1 and MC-LR interaction on genotoxicity and cytotoxicity have been observed on the human liver cell line (HL7702) in vitro [138].…”
Section: Toxicological Interactions Of Aflatoxins With Other Contaminantsmentioning
confidence: 99%